2018
DOI: 10.1186/s12864-018-4558-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel loci associated with maturity and yield traits in early maturity soybean plant introduction lines

Abstract: BackgroundTo continue to meet the increasing demands of soybean worldwide, it is crucial to identify key genes regulating flowering and maturity to expand the cultivated regions into short season areas. Although four soybean genes have been successfully utilized in early maturity breeding programs, new genes governing maturity are continuously being identified suggesting that there remains as yet undiscovered loci governing agronomic traits of interest. The objective of this study was to identify novel loci an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 64 publications
8
35
2
1
Order By: Relevance
“…Our previous study based on evaluation of 120 soybean accessions in three different regions of Kazakhstan (Abugalieva et al, 2016) has confirmed the results of observations in other parts of the world (ContrerasSoto et al, 2018;Copley et al, 2018), which underline the importance of suitable flowering time for plant adaptation in a particular environmental niche.…”
Section: Gwas Of a Soybean Breeding Collection From South East And Sosupporting
confidence: 69%
“…Our previous study based on evaluation of 120 soybean accessions in three different regions of Kazakhstan (Abugalieva et al, 2016) has confirmed the results of observations in other parts of the world (ContrerasSoto et al, 2018;Copley et al, 2018), which underline the importance of suitable flowering time for plant adaptation in a particular environmental niche.…”
Section: Gwas Of a Soybean Breeding Collection From South East And Sosupporting
confidence: 69%
“…GWAS has been conducted to identify markers associated with agronomic traits in soybean [2,3]. To date, more than 60 loci found through GWAS have been reported to be associated with maturity in soybean [4][5][6][7][8][9]. These loci are distributed across the soybean genome with chromosome 16 having the highest number of signi cant loci (https://www.soybase.org/).…”
Section: Introductionmentioning
confidence: 99%
“…GWAS has been conducted to identify markers associated with agronomic traits in soybean (Cao et al 2017;Yao et al 2015). To date, more than 60 loci found through GWAS have been reported to be associated with maturity in soybean (Copley et al 2018;Fang et al 2017;Hu et al 2014;Sonah et al 2015;Zhang et al 2015a;Zuo et al 2013). These loci are distributed across the soybean genome with chromosome 16 having the highest number of significant loci (https://www.soybase.org/).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers associated with seed weight have been previously investigated in soybean. GWAS identified a total of more than 95 loci controlling seed weight with chromosome 4 harboring 12 loci (Contreras-Soto et al 2017;Copley et al 2018;Hao et al 2012;Hu et al 2014;Sonah et al 2015;Wang et al 2016;Yan et al 2017;Zhang et al 2015b;Zhang et al 2016;Zhou et al 2015). Glyma11g03360, Glyma11g03430, Glyma11g05760, Glyma18g05240, Glyma18g43500, Glyma18g43500, Glyma.03g166700, Glyma.11g164700, Glyma.11g164700, LOC100784416, Glyma05g09390, Glyma.07g076800, Glyma10g28250, Glyma14g08050, Glyma14g08280, Glyma19g33421, Glyma19g33550, and Glyma19g35180 have been reported as potential candidate genes for seed weight in soybean (Contreras-Soto et al 2017;Wang et al 2016;Zhang et al 2015;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation